2021
DOI: 10.3389/fmed.2021.718922
|View full text |Cite
|
Sign up to set email alerts
|

Digital Approaches for a Reliable Early Diagnosis of Psoriatic Arthritis

Abstract: Psoriatic arthritis (PsA) is a chronic inflammatory disease that develops in up to 30% of patients with psoriasis. In the vast majority of cases, cutaneous symptoms precede musculoskeletal complaints. Progression from psoriasis to PsA is characterized by subclinical synovio-entheseal inflammation and often non-specific musculoskeletal symptoms that are frequently unreported or overlooked. With the development of increasingly effective therapies and a broad drug armamentarium, prevention of arthritis developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…Fagni et al. ( 34 ) reviewed the applications in the field of mHealth for early intercepting psoriatic arthritis patients. In particular, the authors identified the “Joint Pain Assessment Scoring Tool” (JPAST), a European Union-funded project on digital health, as a promising digital prognostic program that integrates PROMs (patient symptom checker inputs) with biological (serological and genetic) data.…”
Section: Resultsmentioning
confidence: 99%
“…Fagni et al. ( 34 ) reviewed the applications in the field of mHealth for early intercepting psoriatic arthritis patients. In particular, the authors identified the “Joint Pain Assessment Scoring Tool” (JPAST), a European Union-funded project on digital health, as a promising digital prognostic program that integrates PROMs (patient symptom checker inputs) with biological (serological and genetic) data.…”
Section: Resultsmentioning
confidence: 99%
“…Smartphone sensor-based measurements have demonstrated clinical validity for remote patient symptom measurement in Parkinson’s Disease 22 , multiple sclerosis 23 , rheumatoid arthritis, 24,25,26 , diabetes 27 and many others, 28 but no validated toolset exists for psoriasis and psoriatic arthritis. 29…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in daily routine of various health care systems around the world, the possibilities for the creation of a predictive models of PsA development are limited, and many obstacles have been reported ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an extensive innovation in digitalization in rheumatology has occurred. The World Health Organization (WHO) defined “e-Health”, a collective term defined as “use of information and communications technology in support of health and health-related fields“ ( 14 ). This digital revolution included electronic health records, telemedicine and virtual visits, wearable technology, mobile health, artificial intelligence (AI), and machine learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation